PENGARUH PEMBERIAN RUMPUT RAJA (Pennisetum purpupoides) DAN TEBON JAGUNG TERHADAP KECERNAAN BAHAN KERING DAN BAHAN ORGANIK PADA SAPI PO PEDET JANTAN - ., nasriya; Tuturoong, Ronny A.V; Kaunang, Ch. L.; Malalantang, S. S.; Tindangan, M. M. (ZOOTEC, 2016)
THE EFFECTS OF OFFERING KING GRASS (Pennisetum purpupoides) AND CORN  STOVER ON DRY MATTER AND  ORGANIC MATTER OF ONGOLE CROSS BREED STEER CALVES. A research has been conducted to evaluate the effects of offering king grass (Pennisetum purpupoides) and corn stover as ingredients for ration formulating on dry matter and organic matter digestibility of ongole cross breed steer calves. Five ongole cross breed steer calves with about 100 kg body weight were used in this experiment. Latin square design  with 5 tereatments was used. The treatments were rasio of king grass and corn stover; R1 = 100% king grass, R2 = 75% king grass + 25% corn stover, R3 = 50% king grass + 50% corn stover, R4 = 25% king grass + 75% corn stover, R5 100% corn stover.  The variables measured were dry matter and organic matter digestibility. Analysis of variance showed that there were no significant effect of treatments on dry metter and organic matter digestibility. Averages of dry matter digestibility during experiment ranged 56.27% - 59.48%. The highest was 59.48% for R5 (100% corn stover) and the lowest was 56.27% for R1 (100% king grass). Averages of organic matter ranged from 87.64% to 88.72%. The highest organic matter digestibility was on R4 (25% king grass + 75% corn stover) and the lowest organic matter digestibility was on R2 (75% king grass + 25% corn stover). It can be concluded that the best nutritive value was at combination of 25% king grass + 75% corn stover on dry matter and organic matter digestibility of ongole cross breed steer calves. keywords: king grass, corn stover, digestibility, dry matter, organic matter